AGAMA SEBAGAI ALIENASI MANUSIA (Refleksi Kritis Atas Kritik Agama Karl Marx) - Patrisius Seran; David Samuel Latupeirissa (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2021)
The research aims to inventory, critical evaluation, synthesis, and gain a new understanding of Karl Marx's religious criticism. This research is qualitative descriptive using literature study methods. The finding in this study is that marx actually continued feuerbach's religious criticism. According to Marx, Feuerbach's religious criticism was limited to religious criticism. Religious criticism should come down to the situations and conditions that give birth to religion. According to Marx, those who gave birth to religion were man, the human world, society, and the state. Therefore, religious criticism must reach its root, namely criticism of the social conditions of the people who gave birth to religion. Religion as human alienation because in reality human life is always oppressed by other groups of people who are more powerful. To free himself from this exile, Marx concluded that there needed to be a total revolution of oppressed society against the oppressor. The main purpose of this revolution is to free people, especially the oppressed from various alienation, especially social alienation. This, according to Marx, can be achieved by abolishing the system of private ownership of the means of production controlled by upper society. By removing the system of private ownership of the means of production, there will also be classes in society so that a society without classes arises. From this we know that the main purpose of Marx's religious criticism is not religion in se but rather in the concrete real situation of human social life oriented towards exploiting humans. From this we know that the main purpose of Marx's religious criticism is not religion in se but rather in the concrete real situation of human social life oriented towards exploiting humans. Religious criticism was a demonstration of Marx's mind concerned with the living conditions of the workers of his day. The ultimate goal of this criticism is human sociality. There is no more slavery of the workers by the capitalists. Marx wanted an equal life.